Comparative Analysis of Electoral Systems: A Case Study of Electoral Systems in Several Democratic Countries - Ferdinan, Muhammad (Moccasin Journal De Public Perspective, 2024)
This study aims to conduct a comparative analysis of electoral systems in several democratic countries, including the United States, United Kingdom, Germany, and Japan, to understand their structures, mechanisms, and impacts on political representation and governance. Utilizing a qualitative approach, data will be gathered through literature review, policy analysis, and statistical data analysis. The analysis will focus on aspects such as the structure of electoral systems, voting mechanisms, voter participation, political representation, government stability, and the impact of information technology. The findings will provide insights into the differences and similarities between electoral systems in Indonesia and other democratic countries, highlighting factors that influence their performance in achieving effective political representation.